A cut‐off fracture approach for residual stress estimation in thick epoxies: Eine Cut‐off Bruchanalyse zur Eigenspannungabschätzung in dicken Epoxiden. Issue 5 (20th May 2016) - Jochum, C.; Arrigoni, Michel; Boustie, Michel; Grandidier, Jean‐Claude
Abstract : The use of thick carbon fibre reinforced thermosets appears recently for naval and offshore efficient design. However internal residual stresses are developed during the curing of thermosets, as shown by defects like fibre wavinesses, cracks and bubbles, especially with increasing thickness. The understanding of phenomena involved during the curing of thick epoxy was described in a previous work by a by a finite element modeling of the thermal, chemical and mechanical couplings1 . To enable a better quality control, pulsed lasers have recently been used in non‐destructive inspection and characterization of composites and enable quality comparison from a reference stress free sample [2]. The experimental set‐up of the laser shock technique was assessed by simulation approach. Description of material parameters required is presented in the first part of the paper, based on previous experiments and models to identify material parameters for any degree of cure, assuming a dependency to the degree of cure only at room temperature. In this framework, this study presents the effects of epoxy heterogeneity, induced by the curing process of a thick matrix, for internal stress level and damage prediction. The plasticity of the matrix was described by a Ramberg‐Osgood model and an hydrodynamic constitutive law. As a first approach, a simple cut‐off fracture model based on the maximal tensile stress is used to identify the weakest parts of the solid matrix. Simulation comparison with a homogeneous fully cured stress free sample enables a first average residual stress level estimation.